2008
DOI: 10.1007/s10440-008-9209-3
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Equations and Simple Combinatorics

Abstract: A systematic, elementary and pedagogical approach to a class of soliton equations, and to their spectral formulation, is presented. This approach, based on the use of exponential polynomials, follows naturally from a comparison of some simple results for two representatives of the class: the KdV-and the Boussinesq-equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 32 publications
0
79
0
Order By: Relevance
“…Let g = g(x, y, z, t) be a C ∞ function, and the multi-dimensional Bell polynomials are written as [40][41][42][43][44] , , ,…”
Section: Bell Polynomials and Bilinear Equationmentioning
confidence: 99%
“…Let g = g(x, y, z, t) be a C ∞ function, and the multi-dimensional Bell polynomials are written as [40][41][42][43][44] , , ,…”
Section: Bell Polynomials and Bilinear Equationmentioning
confidence: 99%
“…This equation can be viewed as a homogeneous P-condition [8] of weight 6 (the weight of each term being defined as minus its dimension, a weight 3 to ). That means (19) can be written as a linear combination of P-polynomials of weight 6:…”
Section: Case 1 Letmentioning
confidence: 99%
“…In the early 1930s, the classical Bell polynomials were introduced by Bell which are specified by a generating function and exhibiting some important properties [7]. Recently, Lambert and coworkers have proposed a relatively convenient procedure based on Bell polynomials which enables us to obtain bilinear forms, bilinear BTs, Lax pairs, and Darboux covariant Lax pairs for NEEs [8][9][10][11]. It is shown that Bell polynomials play an important role in the characterization of bilinearizable equations and a deep relation between the integrability of an NEE and the Bell polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the phenomena modeled by the NLEEs, some methods have been developed for people to search for the explicit solutions of the NLEEs, such as the inverse scattering transformation [1], Bell polynomials [10][11][12][13][14], Hirota method [15,16], Bäck-lund transformation (BT) [17,18], Darboux transformation [19], and Lie group method [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%